DIAGNOSTICS OF TRANSVERSE MAXILLARY DEFICIENCY - Кобцева, Олена (SWorldJournal, 2025)
Maxillary narrowing occurs in the majority of orthodontic patients and is one of the most common anomalies in orthodontic practice. The purpose of the study. To determine the main tactical steps in the diagnosis of maxillary constriction. Materials and m